An HCCI Control Oriented Model that Includes Combustion Efficiency. Issue 11 (2016) - Ebrahimi, Khashayar; Aliramezani, Masoud; Koch, Charles Robert
Abstract: A control oriented model that includes combustion timing, engine load and combustion efficiency for Homogeneous Charge Compression Ignition (HCCI) engines is developed. In HCCI engines, a lean homogeneous air-fuel mixture auto-ignites due to compression and combustion occurs at lower temperatures compared to spark ignition and diesel engines. The low HCCI combustion temperature results in low NOx level, however unburnt HC and CO levels are high. Higher thermal efficiencies are realized for higher combustion efficiencies when combustion timings is appropriate. First, the effects of valve timing and fueling rate on combustion efficiency are investigated experimentally. Then, the influence of combustion efficiency on HC and CO emissions is studied. A physics based control oriented model of HCCI engine combustion efficiency and emissions for future control design is developed. This model includes the effect of trapped residual gas and fueling rate on combustion timing and output power. The developed model has acceptable accuracy for combustion timing, load and combustion efficiency prediction when compared to experimental data. This model is useful for combustion timing and load control in HCCI engines while simultaneously considering the constraints of combustion efficiency and emission.